The Changing Role of Non-preferential Origin of Goods in World Trade: the Case of the EU - Міщенко, Ілона Володимирівна; Міщенко, І. В.; Mishchenko, Ilona V. (Praha : Enigma Corporation, 2024)
The article examines the issue of non-preferential origin and its role in world trade. It argues that all the instruments used in international trade based on non-preferential origin have different effects on such trade – traditionally negative or restrictive, neutral in terms of not affecting the geography and volume of trade, and positive in terms of achieving certain sustainable development objectives. The latter is rather unclear, so the focus here is on this aspect. Contrary to the prevailing view that only preferential origin, which allows for the application of preferential treatment, is intended to promote and facilitate international trade, it is argued that instruments applied on the basis of non-preferential origin can also have a positive, albeit non-economic, effect. Using the example of the European Union’s trade and customs policies, the paper examines the connection between the non-preferential origin of goods and the solution of such global problems of humanity as the use of forced and child labour, the appropriation of resources and products produced in territories occupied or annexed by aggressor countries and the illegal trade in such goods, the carbonisation of the economy and illegal deforestation. In particular, it is noted that the mechanism of operation of such instruments is linked to additional bans and restrictions on trade in goods originating from problematic territories (annexed or occupied territories, territories where forced labour is used, illegal deforestation, etc.). However, such bans and restrictions contribute to reducing the scale of negative processes through their economic impact on the country in which they occur. It should be noted that the positive impact of such measures is greater the more countries around the world implement them and join in the common contribution to sustainable development.
Mishchenko I. The Changing Role of Non-preferential Origin of Goods in World Trade: the Case of the EU / I. Mishchenko // Evropsky Politicky a Pravni Diskurz. – Praha : Enigma Corporation, 2024. – 11(2). – P. 40-50. URL: https://doi.org/10.46340/eppd.2024.11.2.4
Keywords: non-preferential origin; sustainable development; deep origin; trade defence measures; EU trade and customs policy; most favoured nation treatmen